Effect of Gamma Rays Irradiation and In Vitro Selection on Citrus nobilis (L.) ‘Siam Banyuwangi’ to Huanglongbing (HLB) Disease - Dumaris Priskila Purba; Ali Husni; Alina Akhidaya; Mia Kosmiatin; Agus Purwito (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Siam orange (Citrus nobilis L.) provides great economic value and social importance, despite its susceptibility to Huanglongbing (HLB) disease caused by Ca. Liberabacter sp., classified as specific bacterium phloem vessels marked by the formation of callouses covering plasmodesmata. This research aims to improve the tolerance of Siam orange from Banyuwangi (SB) to HLB disease. The experiment was undertaken by performing a randomized design (CRD) with one factor (irradiation dose). This study consists of two interrelated experiments, which include: induction of embryo mutations with gamma rays irradiation, and in vitro selection of putative mutant. The embryo of SB was irradiated by gamma rays with doses of 0, 45, 50, and 55 Gray. Each treatment was repeatedly undertaken for five times with 20 embryos. After 24 weeks, in vitro selection of putative mutant shoots was screened by HLB pathogen suspension. The observation indicated that treatment of gamma rays in various doses influenced embryo germination. In general, gamma ray irradiation gave significant effects on embryo germination and plant morphological characters. In vitro selection results for putative mutant on doses of 45, 50, and 55 indicated tolerance to HLB pathogen after selection.